MODAL SOSIAL PEDAGANG DURIAN DI KOTA PEKANBARU - Ladea Nazella; Achmad Hidir (CV. Kalimasada Group, 2023)
Durian is one of the fruits that are widely produced to be traded, because it has a taste that is so good to enjoy, the large number of durian fruits during the season on the roadside of a big city makes it easier for durian connoisseurs to enjoy the deliciousness of durian fruit. A descriptive qualitative approach and information selection using purposive sampling techniques, i.e., the acquisition of data from informants based on specific criteria or limitations, are used in this study to identify the components of social capital contained in durian trading business activities. These constraints or qualifications apply to traders who are considered veteran durian sellers. In this study, observation, interviewing, and documenting procedures were employed to collect data. The characteristics of social capital found in the durian trade sector are, according to the study's conclusions.